Effect of ethanol and hydrogen peroxide on poly(3-hydroxybutyrate) biosynthetic pathway in Cupriavidus necator H16 - Obruca, Stanislav; Marova, Ivana; Stankova, Marie; Mravcova, Ludmila; Svoboda, Zdenek (World journal of microbiology & biotechnology, 2010)
Exposition of Cupriavidus necator to ethanol or hydrogen peroxide at the beginning of the stationary phase increases poly(3-hydroxybutyrate) (PHB) yields about 30%. Hydrogen peroxide enhances activity of pentose phosphate pathway that probably consequently increases intracellular ratio NADPH/NADP(+). This effect leads to stimulation of the flux of acetyl-CoA into PHB biosynthetic pathway and to an increase of enzymatic activities of β-ketothiolase and acetoacetyl-CoA reductase while activity of PHB synthase remains uninfluenced. During ethanol metabolisation, in which alcohol dehydrogenase is involved, acetyl-CoA and reduced coenzymes NAD(P)H are formed. These metabolites could again slightly inhibit TCA cycle while flux of acetyl-CoA into PHB biosynthetic pathway is likely to be supported. As a consequence of TCA cycle inhibition also less free CoA is formed. Similarly with hydrogen peroxide, activities of β-ketothiolase and acetoacetyl-CoA reductase are increased which results in over-production of PHB. Molecular weight of PHB produced under stress conditions was significantly higher as compared to control cultivation. Particular molecular weight values were dependent on stress factor concentrations. This could indicate some interconnection among activities of β-ketothiolase, acetoacetyl-CoA reductase and PHB molecular weight control in vivo.